The Effect of Prohexadione-Ca on Starch Content of Potato (Solanum tuberosum) G0 Median in Medium Plains - Dewi Hernawati; Tati Krinstanti; Edi Kusnadi (Jurnal Biodjati, 2025)
The research conducted is entitled "The Effect of Prohexadione-Ca Concentration on Potato Plant (Solanum tuberosum) G0 Medians Cultivar Tubers in Medium Plains". This study aims to determine the effect of Prohexadione-Ca concentration on potato plant (Solanum tuberosum) G0 Medians Cultivars tubers in Medium Plains and to determine the concentration of Prohexadione-Ca to produce the best quality starch content. This research was conducted at the Rancabango screen house, Tarogong Kaler District, Garut Regency, from July to October 2023. The research method used was an experimental method with a Completely Randomized Design (CRD) using 4 treatments, namely Prohexadione-Ca concentration of 0 ppm (Control), 100 ppm, 150 ppm, and 200 ppm. The parameters measured in this study were two types of parameters, namely supporting and main parameters. Supporting parameters include chlorophyll content, photosynthesis rate, and stomatal conductance, while the main parameter is the potato tuber starch content. The benefits of this research are determining the best quality results of potato tubers from the aspect of potato starch content by planting with the best concentration of prohexadione. The study showed an effect on the potato tuber starch content by administering Prohexadione-Ca. The most effective administration of Prohexadione-Ca to produce the quality of potato tuber starch content in medium plains is at a concentration of 100 ppm with a starch content of 9.35%.